2004
DOI: 10.1016/j.jacc.2004.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of long-range heart rate variability

Abstract: Activity increases SDANN by increasing the range of heart periods. Patients with diminished ventricular function have a reduced SDANN on ambulatory electrocardiograms, possibly and partly because of a higher mean heart rate and reduced variations in physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…These discrepant findings may be due to differences in the assessment of depression, in the techniques of HRV analysis, or in the ability to control for confounding factors. Unlike the current study, community studies have not controlled for physical activity, which was shown to influence ULF and VLF (27,28). Our study overcomes many limitations of previous studies by assessing twin pairs and employing a tight control of activity levels and other environmental factors during HRV recording.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These discrepant findings may be due to differences in the assessment of depression, in the techniques of HRV analysis, or in the ability to control for confounding factors. Unlike the current study, community studies have not controlled for physical activity, which was shown to influence ULF and VLF (27,28). Our study overcomes many limitations of previous studies by assessing twin pairs and employing a tight control of activity levels and other environmental factors during HRV recording.…”
Section: Discussionmentioning
confidence: 83%
“…However, VLF may also be influenced by other neurohormonal influences, such as the renin-angiotensin-aldosterone system, and LF may be influenced by sympathetic influences (28,54). ULF may be affected by day-night changes in heart period, especially when activity is controlled (27,55); these changes, in turn, may be influenced by autonomic activity. Although sympathetic activity is not well measured by HRV (56), our findings suggest that disordered parasympathetic regulation and depression may be linked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for this interpretation comes from a study by Sajadieh et al [97], where associations of 24-h HRV with several RF (e.g. physical activity, smoking) were attenuated when only a 15-min night-time segment of the ECG was analyzed, and a study by Roach [105]. Serrador et al [106] also pointed out that short-term HRV at rest may better reflect intrinsic HRV than longterm HRV which could be affected by variation in physical activity.…”
Section: Behavioural Rfmentioning
confidence: 98%
“…Both SDNN, reflecting all variance, and ULF, reflecting variance below .0033Hz, reflect circadian variation, which is autonomically controlled (33). ULF also reflects non-harmonic variations in heart rate, such as those due to physical activity (41). Physical activity has not been found to influence SDNN (40).…”
Section: Introductionmentioning
confidence: 99%